Answer:
B
Step-by-step explanation:
(c - 2d) (3c - 2d) = c*(3c -2d) - 2d(3c - 2d)
9
yea........ hi how you doinn
Answer:
13
Step-by-step explanation:
where n is the number of terms, a1 is the first term and an is the last term. The sum of the first n terms of an arithmetic sequence is called an arithmetic series . Example 1: Find the sum of the first 20 terms of the arithmetic series if a1=5 and a20=62 .An arithmetic sequence is a sequence where the difference between any two consecutive terms is a constant. ... As with any recursive formula, the initial term of the sequence must be given. An explicit formula for an arithmetic sequence with common difference d is given by an=a1+d(n−1) a n = a 1 + d ( n − 1 ) .
Answer:
circumference = 43.98
Step-by-step explanation:
C=2πr=2·π·7≈43.9823
Brainliest?
Answer:
9
Step-by-step explanation:
40 -100 = 60 and 60 percent of 15 is 9